A novel hierarchical porous carbon-supported MnO2 nanofibers composite with three-dimensional interpenetrating network structure as a high-performance supercapacitor. (20th November 2022) - Bi, Tiantian; Chen, Haobin; Li, Jiaqi; Zhang, Xialan; Lin, Qilang
Highlights: Hierarchical porous carbon (HPC) is obtained with three-dimensional (3D) structure. The HPC with highly fluffy 3D continuous network is found as an ideal support. HPC-supported MnO2 nanofibers composite is achieved as a supercapacitor material. The as-prepared MnO2 @HPC composite has 3D interpenetrating network structure. The MnO2 @HPC composite presents excellent electrochemical performance. Abstract: For improving the conductivity of porous carbon and the utilizations of its pore structures, a hierarchical porous carbon (HPC) had been developed with highly fluffy three-dimensional (3D) continuous network structure. Using the HPC as a support, a novel MnO2 @HPC composite with 3D interpenetrating network structure was prepared as electrode material of supercapacitor via simple hydrothermal method. When the hydrothermal reaction temperature was 100°C, the MnO2 nanofibers (∼5 nm) were uniformly grown on and within the fluffy 3D porous network of the HPC, forming a composite with interpenetrating network structure. The as-prepared composite (MnO2 @HPC-100) exhibited the characteristics of both electric double-layer capacitance and pseudo-capacitance, which had a high specific capacity of 368 F g −1 at a current density of 0.5 A g −1 and 186 F g −1 at 10 A g −1 (50.5% retention). In addition,  the asymmetric supercapacitor device was assembled with a relatively high energy density of 88.2 Wh Kg −1 at a power density of 162 W Kg −1 . The device had a high capacity retention rate of 95% after 10000 cycles, and the coulomb efficiency was stable at 99.7%, showing the excellent stability of the composite. Therefore, the MnO2 @HPC-100 composite has great application prospects in energy storage. Graphical abstract: Image, graphical abstract